(untitled) (Research, Society and Development, 2021)
Pharmacogenetics allows to verify the genetic polymorphisms that influence the success of an oncological pharmacotherapy, therefore, the need for progression in the pharmacogenomic oncological field is evident. This study aims to describe the importance of predictive biomarkers related to pharmacogenetic breast and prostate cancer through a literature review. The search for original articles took place between February and November 2020 in databases such as Pubmed, Scielo, Medline and search directories such as Google Scholar. As for the inclusion criteria, the original articles in English, Portuguese and Spanish published between 2010 and 2020 were included. The search result found 102 articles on the subject, 36 excluded because they were review articles, 22 excluded after reading the abstract and 13 excluded because they did not align with the theme. 31 original articles were selected for which the authors prove the importance of validating independent studies on predictive values ​​of biomarkers for breast and prostate cancer. The conclusion of the analyzed studies suggests that the use of biomarkers makes it possible to predict responses to clinical treatment, appropriate therapeutic conduct where they are associated with better treatment results.